COHESIVE SEDIMENT TRANSPORT MODELING ON INNER AMBON BAY - Yunita A. Noya; Mulia Purba; Alan F. Koropitan; Tri Prartono (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2016)
The presence of cohesive sediment in the water column can reduce light penetration and affect photosynthesis process, and it can be disrupted the primary productivity of aquatic, and sedimentation of coastal waters. The objective of this research was to determine the cohesive sediment distribution pattern and the relationship with sedimentation. MIKE 3 FM modeling was used to understand the process of sediment transport and sedimentation on Inner Ambon Bay. Sediment transport modeling method was divided into two stages: the hydrodynamic modeling (baroclinic) and sediment transport (mud transport) modeling. The model results indicate current patterns in the Inner Ambon Bay is influenced by the tidal factor. Suspended sediment dispersed vertically from the surface to a depth of 30 m with concentration of about 3.5-15 Kg/m3. The maximum consentration of the suspended sediment occurs at head of the bay (around Waiheru, Passo, and Lateri). Model simulations for 30 days showed the rate of erosion is about 1.04-6.15 Kg/m2/s, while in Inner Ambon Bay the erosion about 9.07x10-8Kg/m2/s only occurred in T1 station. Sedimentation associated with the cohesive sediment accumulation and it was shown by bed level. In addition, the simulation showed bed level in sill ranged at 0.01-0.19 cm and 0.47 mm/day on average, while in the Inner Ambon Bay it ranged from 1.75-10.01 cm, and the sedimentation rate was approximately 39.9 mm/day.